Les formations en Conservation-Restauration et le développement de la profession - René Hoppenbrouwers (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article traces the evolution of the conservation-restoration profession as well as the role played by the professional organisations in defining high level training programs (university training programs or equivalent). While stressing the importance of interdisciplinarity, multidisciplinarity and the diffusion of knowledge- and this in particular by means of scientific and Open Access publications, the author outlines the decisive role of ENCORE in the field of education in conservation and restoration at European level.